Santripreneur Dan Tantangan Global: Langkah Pesantren Menaklukkan Zaman - Rahita Rahmadya Waluyo; Muhammad Iqbal; Puji Aulia Ananta; Dila Fairuz Salsabila (4, 2026)
Islamic boarding schools (pesantren), as traditional Islamic educational institutions in Indonesia, are currently at a crucial crossroads between preserving tradition and the demands of global change. In the era of globalization and the Fourth Industrial Revolution, Islamic boarding schools face multidimensional challenges, including the rapid influx of foreign cultures, technological gaps, and the influx of transnational ideologies that have the potential to erode moderate Islamic values. These conditions require Islamic boarding schools to not only survive but also transform adaptively and strategically without losing their identity. To address these dynamics, Islamic boarding schools have begun developing curriculum adaptation strategies that are responsive to current developments. The integration of global expertise, such as digital literacy, foreign language proficiency, and strengthening soft skills, has become a crucial part of reforming the Islamic boarding school education system. The implementation of the Blended Learning model is a significant innovation that enables flexible learning processes, combining traditional methods with digital technology to foster 21st-century skills in students. Furthermore, character building remains a key foundation of Islamic boarding school education. The values ​​of Wasathiyah, or Islamic moderation, are intensively instilled to shape students who are tolerant, inclusive, and nationally minded. Santri are positioned not only as learners but also as agents of change capable of actively contributing to social life. The Santripreneurship program was developed as an effort to build economic independence among santri while strengthening ideological resilience. The analysis shows that through educational diplomacy and international collaboration, Islamic boarding schools have a significant opportunity to strengthen their role as Islamic educational institutions deeply rooted in tradition, yet adaptive and globally minded in responding to the challenges of the times. Abstrak Pesantren sebagai lembaga pendidikan Islam tradisional di Indonesia kini berada pada persimpangan penting antara pelestarian tradisi dan tuntutan perubahan global. Di era globalisasi dan Revolusi Industri 4.0, pesantren dihadapkan pada tantangan multidimensi yang meliputi derasnya arus budaya asing, kesenjangan penguasaan teknologi, serta masuknya ideologi transnasional yang berpotensi mengikis nilai-nilai keislaman moderat. Kondisi ini menuntut pesantren untuk tidak hanya bertahan, tetapi juga bertransformasi secara adaptif dan strategis tanpa kehilangan jati dirinya. Dalam menghadapi dinamika tersebut, pesantren mulai mengembangkan strategi adaptasi kurikulum yang responsif terhadap perkembangan zaman. Integrasi keahlian global, seperti literasi digital, penguasaan bahasa asing, dan penguatan soft skills, menjadi bagian penting dari pembaruan sistem pendidikan pesantren. Penerapan model Blended Learning menjadi salah satu inovasi signifikan yang memungkinkan proses pembelajaran berjalan secara fleksibel, menggabungkan metode tradisional dengan teknologi digital guna menumbuhkan kecakapan abad ke-21 pada diri santri. Di sisi lain, penguatan karakter tetap menjadi fondasi utama pendidikan pesantren. Nilai Wasathiyah atau moderasi Islam ditanamkan secara intensif untuk membentuk santri yang toleran, inklusif, dan berwawasan kebangsaan. Santri tidak hanya diposisikan sebagai peserta didik, tetapi juga sebagai agent of change yang mampu berkontribusi aktif dalam kehidupan sosial. Program Santripreneurship turut dikembangkan sebagai upaya membangun kemandirian ekonomi santri sekaligus memperkuat ketahanan ideologi. Hasil analisis menunjukkan bahwa melalui diplomasi pendidikan dan kolaborasi internasional, pesantren memiliki peluang besar untuk meneguhkan perannya sebagai institusi pendidikan Islam yang berakar kuat pada tradisi, namun tetap adaptif dan berwawasan global dalam menjawab tantangan zaman.